Notes on Sciomyzini (Diptera) of East Africa - Никита Евгеньевич Вихрев; Екатерина Юрьевна Яковлева (Амурский зоологический журнал, 2025)
This study examines two taxonomic groups of Sciomyzini flies from East Africa. First, the new species Pherbellia markovi sp. nov. is described and shown to be related to the Nigerian Pteromicra zariae, with supporting evidence presented for transferring the latter species to the genus Pherbellia. Second, new distribution records are provided for Graphomyzina kivuana, representing the first reports of this species from Ethiopia and Kenya. The study further investigates the content, unusual cosmopolitan distribution patterns, and phylogenetic relationships of the genus Graphomyzina, incorporating both ecological data and molecular phylogenetic analyses. As part of this work, new COI sequences were obtained for two Graphomyzina species and deposited in GenBank. Preliminary results of this study were presented at the XII All-Russian Dipterological Symposium (Saint Petersburg, 21– 24 October 2024).